Weathering steel as a potential source for metal contamination: Metal dissolution during 3-year of field exposure in a urban coastal site. (June 2016) - Raffo, Simona; Vassura, Ivano; Chiavari, Cristina; Martini, Carla; Bignozzi, Maria C.; Passarini, Fabrizio; Bernardi, Elena
Abstract: Surface and building runoff can significantly contribute to the total metal loading in urban runoff waters, with potential adverse effects on the receiving ecosystems. The present paper analyses the corrosion-induced metal dissolution (Fe, Mn, Cr, Ni, Cu) from weathering steel (Cor-Ten A) with or without artificial patinas, exposed for 3 years in unsheltered conditions at a marine urban site (Rimini, Italy). The influence of environmental parameters, atmospheric pollutants and surface finish on the release of dissolved metals in rain was evaluated, also by means of multivariate analysis (two-way and three-way Principal Component Analysis). In addition, surface and cross-section investigations were performed so as to monitor the patina evolution. The contribution provided by weathering steel runoff to the dissolved Fe, Mn and Ni loading at local level is not negligible and pre-patination treatments seem to worsen the performance of weathering steel in term of metal release. Metal dissolution is strongly affected by extreme events and shows seasonal variations, with different influence of seasonal parameters on the behaviour of bare or artificially patinated steel, suggesting that climate changes could significantly influence metal release from this alloy. Therefore, it is essential to perform a long-term monitoring of the performance, the durability and the environmental impact of weathering steel. Graphical abstract: Highlights: The environment of exposure affects metal runoff from weathering steel. Outdoor exposure in a marine urban site was performed to study soluble metal runoff. Both bare and artificially patinated weathering steel were considered. Cor-Ten runoff can significantly contribute to dissolved Fe, Mn, Ni urban loading. Metal dissolution is affected by seasonal variation and extreme weather events. Abstract : Runoff-induced metal dissolution from weathering steel is influenced by seasonal variation and extreme events, and can significantly contribute to Fe, Mn, Ni urban loading.